The Leishmaniases: Old Neglected Tropical Diseases (Springer International Publishing, 2018)
Out of the 20 neglected tropical diseases (NTDs) prioritized by the World Health Organization, the leishmaniases rank in the top 3 among those caused by protozoa. The purpose of this book is to provide the reader with a comprehensive and updated overview of all the aspects of leishmaniasis with a worldwide perspective - authors of many chapters include eminent scientists from both the Old and New Worlds. The chapters cover a wide range of topics, classically organized into biology and epidemiology, followed by clinical and control aspects. Following an introductory chapter intended to take the reader into the leishmaniasis complexity, a chapter on Leishmania taxonomy reports on the most recent advances in molecular and phylogenetic data. Parasite biology is then described in detail by means of two separate chapters devoted to phlebotomine vectors and reservoir hosts, respectively. The medical part of the book begins with a chapter on basic immunology and immunopathology associated with Leishmania infection, followed by a classical chapter on clinical aspects of different disease entities. The complexity of disease case management is presented by means of 3 chapters, respectively on diagnosis, treatment of visceral forms and treatment of tegumentary forms. Finally, the last chapter deals with the available approaches to control leishmaniasis and related public health issues. .